Efecto de la suplementación de 2 aditivos (Lactobacillus acidophillus y flavomicina) sobre la digestibilidad y comportamiento productivo en cuyes durante la fase de crecimiento-engorde. - Monar Gavilánez, Carmen Lisbeth (2018)
In the Bolivar province, Guaranda city, San Simón Parish located at 2850 masl, the evaluation of the supplementation effect of two additives, a probiotic lactobacillus acidophillus at different doses (0.20g, 0.30g, 0.40g) and a flavomycin growth promoter at a dose of (0.16g), on the digestibility and productive parameters in guinea pigs during the growth-fattening phase. For which we propose the following objectives. To establish the effect of flavomycin and lactobacillus acidophillus on the enteric health of guinea pig caeca. To determinate the ideal dose of lactobacillus acidophillus as a supplement in guinea pig feeding, and the same with the digestibility of dry matter, to determinate the economic analysis in the cost / benefit ratio .For the next investigation, 84 male guinea pigs of 45 days of age were used and they were fed for 7 weeks. The completely randomized blocks design (DBCA) was applied with four treatments and three repetitions.We proceeded to supply the food ration previously prepared with the different doses of the probiotic and the dose of the growth promoter every day previously weighed, the animals were weighed weekly for the respective statistical analyzes. Once the investigative work was completed, the respective calculations were made where the respective results were obtained. The guinea pigs fed with different doses of the probiotic and a dose of the growth promoter show the best results, so that the T2 supplied with 0.20 g of probiotic obtained a greater final weight gain of 1360.90, followed by the T3 with a final weight of 1283.00, T1 with 1176.83 and finally T4 with a lower weight of 1019.20. Therefore, it is recommended for the production and feeding of guinea pigs using the probiotic Lactobacillus acidophillus in low doses, since they obtain greater weight gain and less adverse effects that harm production.